The association between nutrient intake and physical activity with nutritional status of undergraduate medical students - Ika Alifa Suryabrata; Witri Ardini; Sity Kunarisasi (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2023)
Background: Malnutrition, especially overnutrition, is a primary adult nutrition problem. Food intake and physical activity have been the primary factors that affect nutritional status. In college students, food consumption and physical activity tend not to be compatible with the recommendation. Objective: To know the association between nutrient intake and physical activity with the nutritional status of undergraduate students in the Faculty of Medicine of the Universitas Islam Negeri (UIN) Syarif Hidayatullah Jakarta.Methods: This study was an analytical cross-sectional at the Faculty of Medicine, UIN Syarif Hidayatullah Jakarta, from August to September 2019. The sample of this study was undergraduate medical students at the Faculty of Medicine UIN Syarif Hidayatullah Jakarta, with as many as 113 students meeting qualified criteria. The sample was chosen with a stratified sampling method. Data was taken using IPAQ (International Physical Activity Questionnaire) for physical activity, food records, and height and body weight measurements. Data was analysed using comparative analysis Results: Our analysis demonstrated an association between nutritional status and adequacy of calorie intake (p = 0.001), as well as macronutrient intake (p = 0.001). There was no association between nutritional status and physical activity (p = 0.737). Conclusion: There was an association between nutrient intake and the nutritional status of undergraduate medical students in the Faculty of Medicine UIN Syarif Hidayatullah Jakarta. On the contrary, there was no association between physical activity and the nutritional status of undergraduate medical students in the Faculty of Medicine UIN Syarif Hidayatullah Jakarta.